2010
DOI: 10.5433/1679-0359.2010v31n2p459
|View full text |Cite
|
Sign up to set email alerts
|

Estudo epidemiológico das dermatofitoses em cães e gatos atendidos no serviço de dermatologia da Faculdade de Medicina Veterinária e Zootecnia da UNESP - Botucatu

Abstract: ResumoO objetivo do presente trabalho foi avaliar os prontuários dos pacientes cuja cultura micológica do pêlo, em meio Ágar Sabouraud dextrose, suplementado com cloranfenicol e ciclohexamida, foi positiva para dermatófitos, e realizar um levantamento da casuística de dermatofitose. Foram avaliados 136 prontuários de pacientes (114 caninos e 22 felinos) com dermatofitose atendidos em período de 54 meses, no Hospital Veterinário da UNESP de Botucatu. Pela análise dos resultados, observou-se que a maioria dos cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 12 publications
5
7
0
13
Order By: Relevance
“…The most frequent agent causing dermatophytosis of dogs was M. canis, with 7.3% (3/41). This finding corroborates with Palumbo et al (2010), who observed 79.7% (102/128) of M. canis positive cases among the animals treated at the Department of Dermatology of the Faculdade de Medicina Veterinária of UNESP, Botucatu-SP. Values followed by different letters differ statistically from each other (*p≤0.05).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The most frequent agent causing dermatophytosis of dogs was M. canis, with 7.3% (3/41). This finding corroborates with Palumbo et al (2010), who observed 79.7% (102/128) of M. canis positive cases among the animals treated at the Department of Dermatology of the Faculdade de Medicina Veterinária of UNESP, Botucatu-SP. Values followed by different letters differ statistically from each other (*p≤0.05).…”
Section: Resultssupporting
confidence: 91%
“…For male dogs, however, the most affected sites (p≤0.05) were the trunk or a generalized presentation. Similar data were found by Palumbo et al (2010), who observed 43% of the dogs presenting generalized lesions. Values followed by different letters differ statistically from each other (*p≤0,05).…”
Section: Resultssupporting
confidence: 89%
“…Os sinais dermatológicos mais listados nos casos suspeitos foram alopecia, descamação, pápulas, crostas e eritema (Figura 2A), além de graus variados de prurido. Esta caracterização clínica Research, Society and Development, v. 9, n. 9, e312997014, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7014 foi semelhante à descrita por vários autores consultados (Balda et al, 2004;Palumbo et al, 2010;Miller et al, 2013;Hnilica & Patterson, 2018). Research, Society and Development, v. 9, n. 9, e312997014, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7014 apresentado alopecia, crostas, descamação e eritema.…”
Section: Resultsunclassified
“…É essencial, também, que o pelo do animal seja higienizado e seco. E não permitir que ele tenha contato com outro do qual não se sabe a procedência (PALUMBO et al, 2010).…”
Section: Profilaxiaunclassified